A Nanofluidic Mixing Device for High-throughput Fluorescence Sensing of Single Molecules. (2017) - Mathwig, Klaus; Fijen, Carel; Fontana, Mattia; Lemay, Serge G.; Hohlbein, Johannes
Abstract: We introduce a nanofluidic mixing device entirely fabricated in glass for the fluorescence detection of single molecules. The design consists of a nanochannel T-junction and allows the continuous monitoring of chemical or enzymatic reactions of analytes as they arrive from two independent inlets. The fluorescently labeled molecules are tracked before, during and after they enter the mixing region, and their reactions with each other are observed by means of optical readout such as Förster Resonance Energy Transfer (FRET). Our method can be used for analyzing the kinetics of DNA annealing in a high-parallelized fashion.